2016
DOI: 10.3126/jmmihs.v2i0.15797
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Phytochemical And Biological Activities of two Grewia Species

Abstract: BackgroundMedicinal plants are currently in considerable significance view due to their special attributes as a large source of therapeutic phytochemicals that may lead to the development of novel drugs. Herbs are staging a comeback and herbal 'renaissance' is happening all over the globe. The herbal products today symbolize safety in contrast to the synthetics that are regarded as unsafe to human and environment. It has been estimated that in developed countries such as United States, plant drugs constitute a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…Likewise, 100% MeOH extract, Fraction B, and GAMF3 dispensed at 300 μ g/mL exerted 32 and 46% inhibition in heat-induced hemolysis when compared with the normal control, respectively. Earlier, Khanal et al [ 33 ] in their study on antiinflammatory activity of G. asiatica fruit extracts—as determined with membrane stabilization assays—reported 81% inhibition at 600 μ g/mL, a finding remarkably like ours.…”
Section: Resultssupporting
confidence: 85%
“…Likewise, 100% MeOH extract, Fraction B, and GAMF3 dispensed at 300 μ g/mL exerted 32 and 46% inhibition in heat-induced hemolysis when compared with the normal control, respectively. Earlier, Khanal et al [ 33 ] in their study on antiinflammatory activity of G. asiatica fruit extracts—as determined with membrane stabilization assays—reported 81% inhibition at 600 μ g/mL, a finding remarkably like ours.…”
Section: Resultssupporting
confidence: 85%
“…The authors also postulated that methanolic and acetone extract enriched with tannin and tannin‐like substances inhibited the growth of several micro‐organisms. This is supported by other research that has also identified significant amounts of tannins in the leaves, stem, and bark of phalsa plants, suggesting these components of the plant may also inhibit various micro‐organisms, and therefore, have the potential to assist in disease prevention (see Antimicrobial potential) (Khanal, Raut, & Kafle, 2016; Sharma & Sisodia, 2009, 2016; Shukla, Sharma, Pathak, & Bajpai, 2016a; Shukla et al, 2016b; Tiwari et al, 2014).…”
Section: Nutritional and Phytochemical Compositionsupporting
confidence: 67%
“…The number of spermatogina "A", spermatogonia "B", spermatocytes and spermatid count were improved in the Grewia asiatica extract group significantly as compare to non-treated Grewia asiatica group in the mice for 30 days Singh et al 2007Grewia asiatica extract increase LPO and decrease GSH level in gamma radiation exposure mice brain Sharma and Sisodia (2010) The fruit protect against radiation-induced alterations in blood of Swiss albino mice Sharma et al 2011Grewia asiatica extract exhibit strong radio protective effect in protein carbonyl assay along with strong radical scavenging activity Table 2) (Abou Zeid, Mohammed, & Sleem, 2015;Akhtar et al, 2018;Babu et al, 2017;Islary et al, 2016;Khanal et al, 2016;Khatune et al, 2016;Sharma & Sisodia, 2009;Srivastava et al, 2012;Shukla et al, 2016a;Siddiqi, Naz, Ahmad, & Sayeed, 2011;Tiwari et al, 2014).…”
Section: Radioprotectivementioning
confidence: 99%
See 1 more Smart Citation
“…in 120 min of extract administration) in comparison with the control while indomethacin presented a relatively higher rate of inhibition to PGE2-induced paw edema i.e., 79% at 100 mg/kg [24]. The last study reported that the traditional use of G. asiatica n-hexane extracts as anti-inflammatory ingredients was justified [62] on account of the extract's ability to significantly stabilize human red blood cells in comparison with diclofenac potassium.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%